Tibial stem extension versus standard configuration in primary cemented total knee arthroplasty: systematic review and meta-analysis - Arash Heidari; Mohammad H. Ebrahimzadeh; Mahla Daliri; Ali Moradi; Mahdieh Sahebi; Masoumeh Sadeghi (Journal of Orthopaedic Surgery and Research)
Abstract Background In order to increase the stability of tibial component in total knee arthroplasty (TKA), intramedullary stem extensions (SE) have been developed. The aim of this systematic review and meta-analysis is to address the critical knowledge gap on post-operative outcomes and complications rate comparison between tibial component with SE compared to the tibial component standard configuration (SC) in primary cemented TKA. Methods We conducted a comprehensive search of online databases, including Pubmed, Embase, ISI Web of science, Cochrane Library, and Scopus, using the following MeSH terms, (total knee arthroplasty) OR (TKA) OR (total knee replacement) AND (Tibial stem) OR (stem extension) OR (long stem). We included clinical studies that compared the tibial SE with no tibial stem (standard configuration) in primary cemented TKA. The important exclusion criteria were studies on revision (secondary) TKA, un-cemented arthroplasty, high level constrained implants, TKA with tibial augment & tibial bone graft, TKA with femoral stems, studies on short tibial keel (shorter than SC), without any tibial keel, studies with less than 12 months of follow-up. Knee Society Score (KSS) functional and clinical scores were considered as clinical outcomes along with tibial loosening and implant survival rate. The retrieved studies were assessed for methodological quality using Cochrane Collaborations tool for assessing the risk of bias in randomized trials (ROB) and Cochrane Risk of Bias in Non-Randomized Studies—of Interventions (ROBINS-I) tools. Weighted mean difference (WMD) with 95% confidence interval (CI) was calculated using random-effects meta-analysis taking into account for heterogeneity. Results A total of 223,743 patients (223,766 knees) from 15 articles were included. The risk of tibial aseptic loosening is 54% lower on average in SE group in comparison with SC group (RR: 0.46; 95% CI: 0.29 to 0.74), which is more notable among obese class I patients (RR: 0.47; 95% CI: 0.28 to 0.78), but not significantly different among obese class II patients (RR: 0.58; 95% CI: 0.19 to 1.78). KSS functional and clinical score increased 3.85 score (95% CI: 1.52 to 6.18), and 1,24 scores (95% CI: − 0.22 to 2.70) among patients in SE group, respectively. The survival rate was 1.04 times greater in the SE group. There was no notable difference in terms of knee deformity (hip-knee-ankle angle) correction, all cause secondary procedure, and complications rate between the two groups. Conclusion The meta-analysis of post-operative functional scores and tibial loosening rate indicates a preference for tibial SE over the SC in primary cemented TKA. Some studies were rated as having a fair to critical risk of bias during the quality assessment. To strengthen the evidence and improve the applicability of our findings in clinical practice, future high-quality studies are required.